Too much of a good thing? Evidence that fertilizer subsidies lead to overapplication in Egypt - Kurdi, Sikandra; Mahmoud, Mai; Abay, Kibrom A.; Breisinger, Clemens (International Food Policy Research Institute, 2020)
As part of a national policy to ensure a certain level of food self-sufficiency in strategic crops, the government of Egypt subsidizes nitrogen fertilizer directly by distributing quotas of subsidized fertilizers to farmers and indirectly by subsidizing natural gas used by local fertilizer factories. The implication of this subsidy on farmers’ fertilizer demand and productivity remains unknown. Using a detailed agricultural survey collected from smallholder farmers in Upper Egypt, we show that nitrogen fertilizer application rates are substantially in excess of crop-specific agronomic recommendations. We exploit eligibility criteria and other sources of variation to show that farm plots with easier access to the subsidy tend to use more subsidized nitrogen fertilizer and less phosphate fertilizer. Easier access to the subsidy increases use of total nitrogen fertilizer per unit of land, mainly because of the increase in subsidized nitrogen fertilizer. In particular, the fertilizer subsidy program in Egypt is associated with significant overapplication of nitrogen fertilizer. Such overapplication of fertilizer is expected to adversely affect soil, water, and environmental health. Our findings have important policy implications for Egypt and other African countries known for input subsidy programs. As Egypt is currently moving on from the successful implementation of a comprehensive macroeconomic reform program towards sector-level reforms, our results suggest that eliminating fertilizer subsidies is a good place to start.